Outpatient laparoscopic cholecystectomy: home visit versus telephone follow-up - Fallis, Wendy M. (Canadian Medical Association, 2001)
OBJECTIVES: To investigate the post-discharge follow-up required for patients who have undergone laparoscopic cholecystectomy on an outpatient basis and to determine if there was a significant difference in mean concern scores and satisfaction level of patients followed up by a home visit versus a telephone call. DESIGN: Prospective 2-group comparison. SETTING: A 221-bed acute care community hospital in western Canada. PATIENTS: One hundred and forty-nine patients who had undergone laparoscopic cholecystectomy and agreed to be discharged on the day of operation. INTERVENTIONS: Subjects were systematically allocated to receive either a home visit (HV, n = 72) or a telephone call (TC, n = 77) from a registered nurse on the evening of operation. During the follow-up, patient concerns were self-rated, interventions provided by the nurse were recorded, and nurses’ perceptions of the need for the home visit were reported. A 48-hour telephone survey was used to determine patient satisfaction. OUTCOME MEASURES: Patient concern scores, patient satisfaction with follow-up, readmission rates and use of emergency room services within 30 days of operation. RESULTS: Subjects in the TC group had a significantly lower mean concern score (p < 0.001) and were significantly more satisfied with their follow-up (p = 0.034) than those in the HV group. Nurses perceived that 75% of the home visits were not necessary. Readmission rate was less than 1% (1 HV) and use of emergency room services was 6% (3 HV, 6 TC). CONCLUSIONS: Telephone contact is an acceptable method of follow-up for patients who have undergone outpatient laparoscopic cholecystectomy. The call should be made later in the evening on the day of operation or the next morning.